Metallized fiber-reinforced ceramic-based composite material and preparation method thereof

By preparing composite reinforced powder and interface layer on fiber-reinforced ceramic matrix composite material, and combining metallization spraying technology, the problem of inapplicability of existing metallization methods is solved, the bonding performance and coating stability of the metal layer and the matrix material are improved, and it is suitable for the preparation of conformal antennas.

CN119899053AActive Publication Date: 2025-04-29SHANDONG RES & DESIGN ACADEMY OF IND CERAMICS

Patent Information

Application Number
CN202510386652.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2025-04-29
Estimated Expiration
2045-03-31

AI Technical Summary

Technical Problem

The existing metallization method is not suitable for the preparation of conformal antennas of fiber-reinforced ceramic matrix composites, and the metallization process is complex and the equipment dependence is strong, resulting in insufficient bonding performance between the metal layer and the matrix material and poor coating stability.

Method used

The methods of substrate pretreatment, preparation of composite reinforced powder, preparation of interface layers, preparation of metal layers and finishing are adopted. The bonding performance of the interface layer and the alignment accuracy of the metal layer are improved by mixing nanoboro nitride powder, nanohafnium nitride powder, nano tantalum diboride powder and the treatment of silane coupling agent APTES.

Benefits of technology

It effectively improves the bonding performance of the metallized layer and fiber-reinforced ceramic matrix composite material, improves the stability and performance of the coating, and is suitable for the preparation of conformal antennas with special-shaped structures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention provides a metalized fiber-reinforced ceramic-based composite material and a preparation method thereof, and belongs to the field of ceramic-based composite materials. The preparation method of the metalized fiber-reinforced ceramic-based composite material comprises the following steps of pretreatment of the base material, preparation of the composite reinforced powder, preparation of the interface layer, preparation of the metal layer and finish machining. According to the metalized fiber-reinforced ceramic-based composite material and the preparation method thereof, the problem that an existing metalizing method is not suitable for preparing a conformal antenna for the fiber-reinforced ceramic-based composite material can be effectively solved, and the problems that a metalizing process is complex and equipment dependence is high are solved; the bonding performance of the metallization layer and the fiber reinforced ceramic matrix composite material is improved, and the stability of the coating is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of ceramic-based composite materials, in particular to a metallized fiber-reinforced ceramic-based composite material and a preparation method thereof. Background Art

[0002] With the continuous development of aircraft guidance technology, in the composite guidance mode, passive antennas, as an important part of passive radar seekers, are required to have good impedance matching and radiation characteristics in an ultra-wide frequency band while occupying as little space as possible on the aircraft, and to conform to the aircraft in structure. Therefore, conformal antennas came into being. Conformal antennas refer to radiating antennas that are attached to the surface of an aircraft and conform to it. They are usually installed on high-speed aircraft platforms such as aircraft, missiles, and satellites. Conformal antennas have the characteristics of not destroying the aircraft's external structure and aerodynamics, and are one of the research hotspots in the field of aircraft antennas.

[0003] Specifically, conformal antennas generally integrate radiating antennas with the ceramic cover (window) of the aircraft. They are small, flexible to install, and easy to feed. They can also effectively solve the problem of insufficient direction finding distance and angle of current embedded passive antennas. Currently, passive antenna covers (windows) are mostly fiber-reinforced ceramic matrix composites, and the key to conformal antenna preparation technology is that the metal radiating unit (metal layer) can be well combined with the fiber-reinforced ceramic matrix composite to meet the requirements of aerodynamic thermal environment tolerance and welding.

[0004] According to the survey, in the preparation of existing conformal antennas, the main methods for metallization on the surface of ceramic materials are: thin film method, thick film method, direct copper coating method, laser technology, etc. The thin film method is divided into chemical plating, physical evaporation, chemical vapor deposition, vacuum ion plating (including magnetron sputtering, cathode arc ion plating) and other technologies. The coating is relatively thin and is generally used for the preparation of electrode materials. The thick film method mainly includes screen printing, inkjet printing and other technologies. The direct copper coating method (DBC) is mainly for the metallization technology of aluminum oxide, beryllium oxide, and aluminum nitride substrates.

[0005] However, the existing metallization methods, whether chemical plating or physical evaporation / chemical vapor deposition, have limitations in the metallization process of the aforementioned fiber-reinforced ceramic matrix composites: First, the above methods are only relatively mature for homogeneous ceramic materials. When the fiber-reinforced ceramic matrix composite is used as the matrix, there is a problem of insufficient bonding performance between the metal layer and the matrix material; second, the existing metallization process is relatively complex, highly dependent on equipment, and has high requirements on the surface and shape of the matrix material. Therefore, the existing metallization method is not suitable for the preparation of conformal antennas for fiber-reinforced ceramic matrix composites.

[0006] Chinese patent CN112552079A discloses using a curved surface applicator to evenly coat silver paste (or palladium silver paste) directly onto the surface of a SiO2f / SiO2 composite material, and then sintering at 750°C to obtain the desired metallized curved surface substrate. However, the bonding strength between the metal layer and the base material in the metallized SiO2f / SiO2 composite material obtained by this method is poor.

[0007] Chinese patent CN109704796A discloses the use of 2D or 2.5D fabric sheets and FSS structural units to form a sandwich structure to prepare a frequency-selective wave-transmitting material. The main steps are to impregnate the fabric sheet with silica sol and dry it to form a prepreg, and then overlap it with an organic film with an FSS structure in sequence to form a combined body of the sandwich structure, and finally impregnate the whole with silica sol, dry it, shape it, and sinter it to obtain a low-density product with an FSS structure between the layers. However, due to the limitations of this process, the alignment accuracy between the metal layers is difficult to control, especially for complex structures such as curved surfaces, resulting in the inability to effectively guarantee its related performance and making it unsuitable for the preparation of conformal antennas with special-shaped structures.

[0008] Chinese patent CN106630979A discloses a method for preparing a metallized layer on a fiber-reinforced ceramic composite material. First, a modified layer (quartz glass, lithium aluminum silicon, barium aluminum silicon, cordierite, etc.) is prepared on the surface of the composite material by a plasma spraying process, and then a metallized surface layer is prepared by physical sputtering or a slurry method. However, in order to improve the bonding performance between the metallized layer and the base material, the required modified layer is relatively thick (about 100 μm), which is easy to crack on special-shaped products or large-sized products and has poor stability. In addition, the preparation process still needs to rely on plasma spraying equipment, and the production cost is high.

[0009] Therefore, in view of the problem that the existing metallization method is not suitable for the preparation of conformal antennas for fiber-reinforced ceramic-based composites, and the problem that the metallization process is complicated and highly equipment-dependent, a metallization method that is effective and suitable for conformal antennas for fiber-reinforced ceramic-based composites is provided to improve the bonding performance between the metallization layer and the fiber-reinforced ceramic-based composite material and improve the stability of the coating. It has important technical significance and research value, and provides technical support for the further research and development and expansion of conformal antennas. Summary of the invention

[0010] In order to solve the technical problems existing in the prior art, the present invention provides a metallized fiber-reinforced ceramic-based composite material and a preparation method thereof, which effectively overcomes the problem that the existing metallization method is not suitable for the preparation of conformal antennas for fiber-reinforced ceramic-based composite materials, as well as overcomes the problems of complex metallization process and strong equipment dependence, improves the bonding performance between the metallization layer and the fiber-reinforced ceramic-based composite material, and improves the stability of the coating.

[0011] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows: A method for preparing a metallized fiber-reinforced ceramic-based composite material comprises the following steps: pretreatment of substrate, preparation of composite reinforcement powder, preparation of interface layer, preparation of metal layer, and fine processing; The substrate pretreatment is to process the fiber-reinforced ceramic matrix composite material to a predetermined size of the conformal antenna, and then obtain a pretreated substrate after surface polishing and defect repair; In the preparation of the composite reinforced powder, nano boron nitride powder, nano hafnium nitride powder and nano tantalum diboride powder are uniformly mixed to obtain a premixed powder; the premixed powder is treated with a silane coupling agent APTES to obtain a composite reinforced powder; The interface layer is prepared by uniformly mixing the interface layer coating, solvent and composite reinforcing powder to obtain an interface layer spray coating slurry; spraying the interface layer spray coating slurry onto the surface of the pretreated substrate, drying and sintering, to obtain a substrate with an interface layer formed on the surface; The interface layer coating is a polysilazane coating or a polysiloxane coating; The metal layer is prepared by spraying the metallized spray slurry onto the interface layer surface of the substrate, followed by drying and sintering to obtain a substrate with a metal layer formed on the surface.

[0012] Furthermore, in the substrate pretreatment, defect repair is performed by spot coating the defect with a repair liquid and then sintering; The repair liquid is composed of the following raw materials in parts by weight: 35-45 parts of silica sol, 1-5 parts of boric acid, and 55-65 parts of submicron ceramic powder; The submicron ceramic powder is selected from: silicon oxide, aluminum oxide, and mullite.

[0013] Furthermore, in the preparation of the composite reinforced powder, the premixed powder is put into an ethanol solution, stirred and heated to 55-60°C, kept warm and the silane coupling agent APTES is dripped in; after the addition of the silane coupling agent APTES is completed, the stirring is continued for 4-5 hours, and the solid is separated, and the solid is washed with water and then dried to obtain the composite reinforced powder.

[0014] Preferably, in the preparation of the composite reinforced powder, the mass ratio of nano boron nitride powder, nano hafnium nitride powder, and nano tantalum diboride powder is 3-3.5:5-6:1-1.2; The mass ratio of the premixed powder to the silane coupling agent APTES is 1:0.2-0.25.

[0015] Preferably, in the preparation of the interface layer, the mass ratio of the interface layer coating, the solvent, and the composite reinforcing powder is 84-88:32-40:12-16; The spraying pressure of the interface layer spray slurry is 0.2-0.3MPa, and the spraying weight gain is controlled to be 100cm2 The spray weight on the pre-treated substrate surface is 0.4-0.6g.

[0016] Preferably, in the preparation of the interface layer, the drying temperature is 85-100°C and the drying time is 0.5-1h; The sintering temperature is 750-850℃ and the sintering time is 15-30min; The thickness of the interface layer is 6-10 μm.

[0017] Preferably, in the preparation of the metal layer, the metallization spray coating slurry contains metal slurry and a diluent; The metal slurry is one of the following: silver slurry, gold slurry, platinum slurry, silver-palladium alloy slurry; The diluent is an ethanol or propanol solution of butyl carbitol or terpineol; The mass ratio of metal slurry to diluent is 65-75:25-35.

[0018] Preferably, in the preparation of the metal layer, the spraying pressure of the metallization spray slurry is 0.2-0.3 MPa, and the spraying weight gain is controlled to be 100 cm 2 The spray weight on the interface layer surface is 1-1.5g; The drying temperature is 120-150°C and the drying time is 0.5-1h; The sintering temperature is 750-850℃ and the sintering time is 10-15min; The thickness of the metal layer is 8-15 μm.

[0019] Furthermore, the finishing process uses laser etching to finish the metal layer of the conformal antenna radiation area to obtain a metallized fiber-reinforced ceramic matrix composite material for the conformal antenna; The laser etching uses a 3D galvanometer to control the laser direction and uses a picosecond laser for etching; The laser power of the laser etching is 2-5W, the linear speed is 300-500mm / s, and the etching times are 2-4 times.

[0020] A metallized fiber-reinforced ceramic-based composite material prepared by the above method.

[0021] Compared with the prior art, the present invention has the following beneficial effects: (1) The preparation method of the metallized fiber-reinforced ceramic matrix composite material of the present invention comprises processing the fiber-reinforced ceramic matrix composite material to a predetermined size of a conformal antenna cover (window) as required, obtaining a pre-treated substrate, and then uniformly mixing nano-boron nitride powder, nano-hafnium nitride powder, and nano-tantalum diboride powder and treating them with a silane coupling agent APTES to obtain a composite reinforced powder; modifying the pre-mixed powder with a silane coupling agent APTES to improve its dispersibility in the interface layer spray slurry and improve its bonding performance with the interface layer coating. Then the composite reinforced powder is mixed with the interface layer coating (polysilazane coating or polysiloxane coating) to obtain the interface layer spray slurry, which is then sprayed onto the surface of the pretreated substrate to form an interface layer; and the addition of the composite reinforced powder inhibits shrinkage, reduces internal stress, and improves the thermal stability, thermal shock resistance and mechanical properties of the interface layer; and improves the bonding performance of the interface layer with the substrate, and forms a mechanical interlock and inhibits interface peeling through the anchoring effect of the composite reinforced powder on the surface of the pretreated substrate; at the same time, through the setting of the interface layer, the wettability problem of the metal layer and the composite material is effectively improved, and the bonding performance of the coating and the substrate is optimized. Then the metallized spray slurry is coated on the interface layer coating area to form a metal layer, and finally, after fine processing, a metallized fiber-reinforced ceramic matrix composite material is obtained; the aforementioned technical means cooperate with each other and work synergistically, which can effectively overcome the problem that the existing metallization method is not suitable for the preparation of conformal antennas for fiber-reinforced ceramic matrix composite materials, as well as the problem that the metallization process is complex and highly dependent on equipment, improve the bonding performance of the metallization layer and the fiber-reinforced ceramic matrix composite material, and improve the stability of the coating.

[0022] (2) The preparation method of the metallized fiber-reinforced ceramic-based composite material of the present invention utilizes the method of ceramicizing the precursor to form an interface layer on the surface of the fiber-reinforced ceramic-based composite material. The preparation method is simple and has better bonding strength. At the same time, the ceramicizing reaction can solidify and strengthen the exposed fiber bundles on the surface of the fiber-reinforced ceramic-based composite material, further optimizing the bonding performance between the coating and the substrate.

[0023] (3) The preparation method of the metallized fiber-reinforced ceramic-based composite material of the present invention has strong process applicability. By selecting the interface layer material and the metal layer material, a coating with specific temperature resistance can be prepared on the surface of different ceramic-based composite materials, which provides a technical option for the subsequent research and development of conformal antennas. In addition, the preparation method of the present invention is simple, easy to operate, and has low equipment requirements. It can be prepared using traditional cold spraying equipment and muffle furnace sintering equipment, without the need for complex process equipment, and is conducive to large-scale industrial production. DETAILED DESCRIPTION

[0024] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific embodiments of the present invention are now described. It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those of ordinary skill in the art to which the present invention belongs.

[0025] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, "first", "second", etc. are used to distinguish similar objects, and are not used to describe a specific order or sequence. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0026] The embodiment of the present invention provides a method for preparing a metallized fiber-reinforced ceramic-based composite material, which is achieved through the following technical scheme: first, the fiber-reinforced ceramic-based composite material is processed to the design size of a conformal antenna cover (window) as required, and then the interface layer spray slurry is coated on the metal radiation area required by the antenna by spraying, and the fiber-reinforced ceramic-based composite material with an interface layer is obtained after drying and sintering; the metallized spray slurry is coated on the interface layer coating area by spraying again, and the metallized fiber-reinforced ceramic-based composite material is obtained after drying and sintering; finally, according to the requirements of the conformal antenna, the antenna radiation unit of the obtained metallized fiber-reinforced ceramic-based composite material is finely processed by laser processing, and finally the metallized fiber-reinforced ceramic-based composite material (conformal antenna cover, window, etc.) that can be used for conformal antennas is obtained.

[0027] The method for preparing the metallized fiber-reinforced ceramic-based composite material comprises the following steps: pretreatment of substrate, preparation of composite reinforcement powder, preparation of interface layer, preparation of metal layer and fine processing.

[0028] The method for pretreating the substrate is to select a fiber-reinforced ceramic-based composite material according to the requirements of the conformal antenna for temperature resistance, dielectric properties, and mechanical properties; process the fiber-reinforced ceramic-based composite material to a predetermined size of the conformal antenna, then polish and grind its surface, repair defects, and use paper tape to shield and protect the non-working area to obtain a pretreated substrate.

[0029] In the substrate pretreatment, the fiber-reinforced ceramic-based composite materials are all existing ceramic-based composite materials, including: quartz fiber-reinforced quartz composite materials, quartz fiber-reinforced silicon nitride composite materials, alumina fiber-reinforced alumina composite materials, and mullite fiber-reinforced alumina composite materials.

[0030] The polishing and grinding is to polish the surface of the fiber-reinforced ceramic-based composite material with 800-1000 mesh sandpaper to remove fiber burrs caused by machining on the material surface; the defect repair is to apply a repair liquid to the defect, and then sinter at a temperature of 650-750°C for 1-2 hours to repair fiber breakage, dents caused by peeling, and material shortages caused by machining on the material surface.

[0031] The repair liquid is composed of silica sol, boric acid, and submicron ceramic powder; the submicron ceramic powder is selected from silicon oxide, aluminum oxide, and mullite. The weight percentage of each raw material in the repair liquid is 35-45 parts of silica sol, 1-5 parts of boric acid, and 55-65 parts of submicron ceramic powder.

[0032] The method for preparing the composite reinforced powder comprises the following steps: adding nano boron nitride powder, nano hafnium nitride powder and nano tantalum diboride powder into a ball mill, controlling the ball-to-material water ratio to be 6-6.5:1:0.6-0.7, and the ball milling speed to be 120-180 rpm; after ball milling for 20-30 min, taking out the ball milled material and drying it to obtain a premixed powder; then adding the premixed powder into an ethanol solution (volume concentration of 70-75%) with a mass of 5-6 times, heating the solution to 55-60° C. under stirring at 50-80 rpm, keeping the temperature and dripping in a silane coupling agent APTES; after the silane coupling agent APTES is dripped, the solution is kept warm and stirred for 4-5 h, filtering to obtain a solid, washing the solid with water and drying it to obtain the composite reinforced powder.

[0033] In the preparation of the composite reinforced powder, the mass ratio of nano boron nitride powder, nano hafnium nitride powder and nano tantalum diboride powder is 3-3.5:5-6:1-1.2; The mass ratio of the premixed powder to the silane coupling agent APTES is 1:0.2-0.25.

[0034] The method for preparing the interface layer comprises: uniformly mixing the interface layer coating, solvent and composite reinforcing powder to obtain the interface layer spray coating slurry; spraying the interface layer spray coating slurry onto the surface of the pretreated substrate by using a spray gun under the condition of a spraying pressure of 0.2-0.3 MPa, and controlling the spraying weight gain (per 100 cm 2 The spraying amount on the surface of the pretreated substrate is 0.4-0.6g); after spraying, it is placed in an oven, dried at 85-100℃ for 0.5-1h, transferred to a muffle furnace, and sintered at 750-850℃ for 15-30min to ceramicize the interface layer material to obtain a substrate with an interface layer formed on the surface, and the thickness of the interface layer is 6-10μm.

[0035] In the preparation of the interface layer, the interface layer coating is a polysilazane coating or a polysiloxane coating; the solvent is toluene or xylene; The mass ratio of the interface layer coating, solvent, and composite reinforcing powder is 84-88:32-40:12-16; The spray gun used for spraying can be the existing atomizing spray guns of models W-71, W-77, W-101, and W-201.

[0036] The method for preparing the metal layer comprises: mixing the metal slurry and the diluent evenly to obtain the metallized spray coating slurry; spraying the metallized spray coating slurry onto the interface layer surface of the substrate by spraying at a spraying pressure of 0.2-0.3 MPa using a spray gun, and controlling the spraying weight gain (per 100 cm 2 The spraying amount of the pretreated substrate surface is 1-1.5g); after spraying, it is placed in an oven, dried at 120-150°C for 0.5-1h, transferred to a muffle furnace, and sintered at 750-850°C for 10-15min to obtain a substrate with a metal layer formed on the surface, and the thickness of the metal layer is 8-15μm.

[0037] In the preparation of the metal layer, the metal slurry is one of the following: silver slurry, gold slurry, platinum slurry, silver-palladium alloy slurry; the metal slurry is a conventional commercial product, composed of corresponding metal powder, epoxy resin, glass powder and solvent; the mass fraction of the metal powder in the metal slurry is 75-85wt%; The diluent is an ethanol (or propanol) solution of butyl carbitol (or pineol); the mass fraction of butyl carbitol (or pineol) in the diluent is 8-15%; The mass ratio of metal slurry to diluent is 65-75:25-35; The spray gun used for spraying can be the existing atomizing spray guns of models W-71, W-77, W-101, and W-201.

[0038] The finishing method is to finish the metal layer of the conformal antenna radiation zone by laser etching to obtain a metalized fiber-reinforced ceramic-based composite material for the conformal antenna.

[0039] In the finishing process, the laser etching uses a 3D galvanometer to control the laser direction, and a picosecond laser is used for etching; the laser power is controlled to be 2-5W, the linear speed is 300-500mm / s, and the etching times are 2-4 times.

[0040] The embodiment of the present invention also provides a method for preparing the metallized fiber-reinforced ceramic-based composite material prepared by the above method.

[0041] The present invention is further described below in conjunction with some specific embodiments.

[0042] Example 1 This embodiment provides a method for preparing a metallized fiber-reinforced ceramic matrix composite material, specifically: 1. Substrate pretreatment The fiber-reinforced ceramic matrix composite material is processed to a predetermined size of a conformal antenna, and then its surface is polished and ground, and defects are repaired. Then, paper tape is used to shield and protect the non-working area to obtain a pretreated substrate.

[0043] Wherein, the fiber-reinforced ceramic-based composite material is a quartz fiber-reinforced quartz composite material.

[0044] The polishing and grinding is to polish the surface of the fiber-reinforced ceramic-based composite material with 1000 mesh sandpaper to remove fiber burrs caused by machining on the material surface; the defect repair is to apply a repair liquid to the defect, and then sinter at 650°C for 1 hour to repair fiber breakage, dents caused by peeling and material shortages caused by machining on the material surface.

[0045] The repair liquid is composed of silica sol, boric acid, and submicron ceramic powder; the submicron ceramic powder is silicon oxide. The mass parts of each raw material in the repair liquid are 35 parts of silica sol, 1 part of boric acid, and 55 parts of submicron ceramic powder.

[0046] 2. Preparation of composite reinforced powder Nano boron nitride powder, nano hafnium nitride powder and nano tantalum diboride powder were put into a ball mill, and the ball-to-material water ratio was controlled to be 6:1:0.6, and the ball mill speed was 120 rpm. After ball milling for 30 minutes, the ball milled material was taken out and dried to obtain a premixed powder; then the premixed powder was put into 5 times the mass of ethanol solution (volume concentration 70%), and the temperature was raised to 55°C under stirring at 50 rpm, and the silane coupling agent APTES was dripped in while being kept warm; after the addition of the silane coupling agent APTES was completed, the stirring was continued for 4 hours, and the solid was filtered to obtain the solid, and the solid was washed with water and dried to obtain a composite reinforced powder.

[0047] Among them, the mass ratio of nano boron nitride powder, nano hafnium nitride powder and nano tantalum diboride powder is 3:5:1.

[0048] The mass ratio of the premixed powder to the silane coupling agent APTES is 1:0.2.

[0049] 3. Preparation of interface layer The interface layer coating, solvent and composite reinforcing powder are mixed evenly to obtain the interface layer spray coating slurry; the interface layer spray coating slurry is sprayed onto the surface of the pretreated substrate by a spray gun under a spray pressure of 0.2 MPa, and the spraying weight gain (per 100 cm 2The spraying amount on the surface of the pretreated substrate is 0.4 g); after spraying, it is placed in an oven, dried at 85°C for 0.5 h, and then transferred to a muffle furnace and sintered at 750°C for 15 min to ceramicize the interface layer material to obtain a substrate with an interface layer formed on the surface, and the thickness of the interface layer is 6.1 μm.

[0050] Wherein, the interface layer coating is polysilazane coating; and the solvent is toluene.

[0051] The mass ratio of the interface layer coating, the solvent and the composite reinforcing powder is 84:32:12.

[0052] The spray gun model used for spraying is W-101.

[0053] 4. Preparation of metal layer The metal slurry and the diluent are mixed evenly to obtain a metallized spray slurry; the metallized spray slurry is sprayed onto the interface layer surface of the substrate by a spray gun under a spray pressure of 0.2 MPa, and the spray weight gain (per 100 cm 2 The spraying amount on the surface of the pretreated substrate is 1g); after spraying, it is placed in an oven, dried at 120°C for 0.5h, transferred to a muffle furnace, and sintered at 750°C for 10min to obtain a substrate with a metal layer formed on the surface, and the thickness of the metal layer is 8.0μm.

[0054] The metal slurry is a silver slurry, which is composed of silver powder, epoxy resin, glass powder and solvent, and is a conventional commercially available product; the mass fraction of the silver powder in the metal slurry is 80wt%.

[0055] The diluent is an ethanol solution of butyl carbitol; the mass fraction of butyl carbitol in the diluent is 9%.

[0056] The mass ratio of metal slurry to diluent is 70:30.

[0057] The spray gun model used for spraying is W-101.

[0058] 5. Finishing The metal layer of the conformal antenna radiation area is finely processed by laser etching to obtain a metallized fiber-reinforced ceramic-based composite material for the conformal antenna.

[0059] Among them, laser etching uses a 3D galvanometer to control the laser direction and uses picosecond laser for etching; the laser power is controlled to 2W, the linear speed is 300mm / s, and the number of etching times is 4 times.

[0060] This embodiment also provides a method for preparing the metallized fiber-reinforced ceramic-based composite material prepared by the aforementioned method.

[0061] Example 2 This embodiment provides a method for preparing a metallized fiber-reinforced ceramic matrix composite material, specifically: 1. Substrate pretreatment The fiber-reinforced ceramic matrix composite material is processed to a predetermined size of a conformal antenna, and then its surface is polished and ground, and defects are repaired. Then, paper tape is used to shield and protect the non-working area to obtain a pretreated substrate.

[0062] Wherein, the fiber-reinforced ceramic matrix composite material is an alumina fiber-reinforced alumina composite material.

[0063] The polishing and grinding is to polish the surface of the fiber-reinforced ceramic-based composite material with 1000 mesh sandpaper to remove fiber burrs caused by machining on the material surface; the defect repair is to apply a repair liquid to the defect, and then sinter at 700°C for 1.5 hours to repair fiber breakage, dents caused by peeling and material shortages caused by machining on the material surface.

[0064] The repair liquid is composed of silica sol, boric acid, and submicron ceramic powder; the submicron ceramic powder is aluminum oxide. The mass percentage of each raw material in the repair liquid is 38 parts of silica sol, 3 parts of boric acid, and 61 parts of submicron ceramic powder.

[0065] 2. Preparation of composite reinforced powder Nano boron nitride powder, nano hafnium nitride powder and nano tantalum diboride powder were put into a ball mill, and the ball-to-material water ratio was controlled to be 6.2:1:0.65, and the ball mill speed was 160 rpm. After ball milling for 25 minutes, the ball milled material was taken out and dried to obtain a premixed powder; then the premixed powder was put into 5.5 times the mass of ethanol solution (volume concentration 72%), and the temperature was raised to 58°C under stirring at 60 rpm, and the silane coupling agent APTES was dripped in while being kept warm; after the addition of the silane coupling agent APTES was completed, the stirring was continued for 4.5 hours, and the solid was filtered to obtain the solid, and the solid was washed with water and dried to obtain a composite reinforced powder.

[0066] Among them, the mass ratio of nano boron nitride powder, nano hafnium nitride powder and nano tantalum diboride powder is 3.3:5.4:1.1.

[0067] The mass ratio of the premixed powder to the silane coupling agent APTES is 1:0.23.

[0068] 3. Preparation of interface layer The interface layer coating, solvent and composite reinforcing powder are mixed evenly to obtain the interface layer spray coating slurry; the interface layer spray coating slurry is sprayed onto the surface of the pretreated substrate by a spray gun under a spray pressure of 0.25 MPa, and the spraying weight gain (per 100 cm 2The spraying amount on the surface of the pretreated substrate is 0.5g); after spraying, it is placed in an oven, dried at 95°C for 0.75h, and then transferred to a muffle furnace and sintered at 800°C for 20min to ceramicize the interface layer material to obtain a substrate with an interface layer formed on the surface, and the thickness of the interface layer is 7.8μm.

[0069] Wherein, the interface layer coating is polysilazane coating; and the solvent is xylene.

[0070] The mass ratio of the interface layer coating, the solvent and the composite reinforcing powder is 85:34:14.

[0071] The spray gun model used for spraying is W-201.

[0072] 4. Preparation of metal layer The metal slurry and the diluent are mixed evenly to obtain a metallized spray slurry; the metallized spray slurry is sprayed onto the interface layer surface of the substrate by a spray gun under a spray pressure of 0.25 MPa, and the spray weight gain (per 100 cm 2 The spraying amount on the surface of the pretreated substrate is 1.3 g); after spraying, it is placed in an oven, dried at 125°C for 0.75 h, and then transferred to a muffle furnace and sintered at 800°C for 12 min to obtain a substrate with a metal layer formed on the surface, and the thickness of the metal layer is 12.3 μm.

[0073] The metal slurry is a silver slurry, which is composed of silver powder, epoxy resin, glass powder and solvent, and is a conventional commercially available product; the mass fraction of the silver powder in the metal slurry is 80wt%.

[0074] The diluent is an ethanol solution of butyl carbitol; the mass fraction of butyl carbitol in the diluent is 9%.

[0075] The mass ratio of metal slurry to diluent is 72:28.

[0076] The spray gun model used for spraying is W-201.

[0077] 5. Finishing The metal layer of the conformal antenna radiation area is finely processed by laser etching to obtain a metallized fiber-reinforced ceramic-based composite material for the conformal antenna.

[0078] Among them, laser etching uses a 3D galvanometer to control the laser direction and uses picosecond laser for etching; the laser power is controlled to 4W, the linear speed is 450mm / s, and the number of etching times is 3 times.

[0079] This embodiment also provides a method for preparing the metallized fiber-reinforced ceramic-based composite material prepared by the aforementioned method.

[0080] Example 3 This embodiment provides a method for preparing a metallized fiber-reinforced ceramic matrix composite material, specifically: 1. Substrate pretreatment The fiber-reinforced ceramic matrix composite material is processed to a predetermined size of a conformal antenna, and then its surface is polished and ground, and defects are repaired. Then, paper tape is used to shield and protect the non-working area to obtain a pretreated substrate.

[0081] Wherein, the fiber-reinforced ceramic-based composite material is a mullite fiber-reinforced alumina composite material.

[0082] The polishing and grinding is to polish the surface of the fiber-reinforced ceramic-based composite material with 1000 mesh sandpaper to remove fiber burrs caused by machining on the material surface; the defect repair is to apply a repair liquid to the defect, and then sinter at 750°C for 2 hours to repair fiber breakage, dents caused by peeling and material shortages caused by machining on the material surface.

[0083] The repair liquid is composed of silica sol, boric acid, and submicron ceramic powder; the submicron ceramic powder is mullite. The mass parts of each raw material in the repair liquid are 45 parts of silica sol, 5 parts of boric acid, and 65 parts of submicron ceramic powder.

[0084] 2. Preparation of composite reinforced powder Nano boron nitride powder, nano hafnium nitride powder and nano tantalum diboride powder were put into a ball mill, and the ball-to-material water ratio was controlled to be 6.5:1:0.7, and the ball mill speed was 180 rpm. After ball milling for 30 minutes, the ball milled material was taken out and dried to obtain a premixed powder; then the premixed powder was put into 6 times the mass of ethanol solution (volume concentration 75%), and the temperature was raised to 60°C under stirring at 80 rpm, and the silane coupling agent APTES was dripped in while being kept warm; after the addition of the silane coupling agent APTES was completed, the stirring was continued for 5 hours, and the solid was filtered to obtain the solid, and the solid was washed with water and dried to obtain a composite reinforced powder.

[0085] Among them, the mass ratio of nano boron nitride powder, nano hafnium nitride powder and nano tantalum diboride powder is 3.5:6:1.2.

[0086] The mass ratio of the premixed powder to the silane coupling agent APTES is 1:0.25.

[0087] 3. Preparation of interface layer The interface layer coating, solvent and composite reinforcing powder are mixed evenly to obtain the interface layer spray coating slurry; the interface layer spray coating slurry is sprayed onto the surface of the pretreated substrate by a spray gun under a spray pressure of 0.3 MPa, and the spraying weight gain (per 100 cm 2The spraying amount on the surface of the pretreated substrate is 0.6 g); after spraying, it is placed in an oven, dried at 100°C for 1 hour, and then transferred to a muffle furnace and sintered at 850°C for 30 minutes to ceramicize the interface layer material to obtain a substrate with an interface layer formed on the surface, and the thickness of the interface layer is 10 μm.

[0088] Wherein, the interface layer coating is polysilazane coating; and the solvent is toluene.

[0089] The mass ratio of the interface layer coating, the solvent and the composite reinforcing powder is 88:40:16.

[0090] The spray gun model used for spraying is W-201.

[0091] 4. Preparation of metal layer The metal slurry and the diluent are mixed evenly to obtain a metallized spray slurry; the metallized spray slurry is sprayed onto the interface layer surface of the substrate by a spray gun under a spray pressure of 0.3 MPa, and the spray weight gain (per 100 cm 2 The spraying amount on the surface of the pretreated substrate is 1.5 g); after spraying, it is placed in an oven, dried at 150° C. for 1 hour, transferred to a muffle furnace, and sintered at 850° C. for 15 minutes to obtain a substrate with a metal layer formed on the surface, and the thickness of the metal layer is 14.8 μm.

[0092] Among them, the metal slurry is platinum slurry, which is composed of platinum powder, epoxy resin, glass powder and solvent, and is a conventional commercially available product; the mass fraction of platinum powder in the metal slurry is 80wt%.

[0093] The diluent is an ethanol solution of butyl carbitol; the mass fraction of butyl carbitol in the diluent is 9%.

[0094] The mass ratio of metal slurry to diluent is 75:25.

[0095] The spray gun model used for spraying is W-201.

[0096] 5. Finishing The metal layer of the conformal antenna radiation area is finely processed by laser etching to obtain a metallized fiber-reinforced ceramic-based composite material for the conformal antenna.

[0097] Among them, laser etching uses a 3D galvanometer to control the laser direction and uses picosecond laser for etching; the laser power is controlled to 5W, the linear speed is 500mm / s, and the number of etching times is 2 times.

[0098] This embodiment also provides a method for preparing the metallized fiber-reinforced ceramic-based composite material prepared by the aforementioned method.

[0099] Comparative Example 1 For the sake of comparison, the method for preparing the metallized fiber-reinforced ceramic matrix composite material of Comparative Example 1 adopts the technical solution of Example 3, except that the step of preparing the composite reinforcing powder is omitted, and the addition of the composite reinforcing powder to the interface layer spray slurry is omitted.

[0100] The coating-related properties of the metallized fiber-reinforced ceramic-based composite materials of Examples 1-3 and Comparative Example 1 were tested respectively. Specifically, the bonding performance between the coating and the substrate at room temperature was tested (specifically refer to GB / T9286-2021); and the bonding performance between the coating and the substrate was tested after the metallized fiber-reinforced ceramic-based composite materials of Examples 1-2 were thermally tested at 850°C / 600s by a quartz lamp (specifically refer to GB / T9286-2021); the bonding performance between the coating and the substrate was tested after the metallized fiber-reinforced ceramic-based composite materials of Example 3 and Comparative Example 1 were thermally tested at 1000°C / 600s by a quartz lamp (specifically refer to GB / T9286-2021).

[0101] At the same time, in the preparation process of the metallized fiber-reinforced ceramic matrix composite materials of Examples 1-3 and Comparative Example 1, the dielectric loss tangent values ​​of the pretreated substrate and the substrate with an interface layer formed on the surface (and the interface layer is removed by laser) are respectively detected, and the difference in the dielectric loss tangent values ​​of the two (i.e., the loss tangent growth rate) is calculated to evaluate the influence of the pretreatment and interface layer process of the present invention on the wave transmission performance of the pretreated substrate. The calculation method of the dielectric loss tangent growth rate of the substrate with an interface layer formed on the surface (and the interface layer is removed by laser) compared with the pretreated substrate is [(dielectric loss tangent value of the substrate with an interface layer formed on the surface (and the interface layer is removed by laser) - dielectric loss tangent value of the pretreated substrate) / dielectric loss tangent value of the pretreated substrate] × 100%. The specific results are as follows:

[0102] Furthermore, the metallized fiber-reinforced ceramic-based composite materials of Examples 1-3 and Comparative Example 1 were placed in a quartz lamp array, and thermal shock cycle tests were performed at 850°C (Examples 1-2) and 1000°C (Example 3, Comparative Example 1) in an air gas environment. Specifically, the metallized fiber-reinforced ceramic-based composite materials of Examples 1-2 in the quartz lamp array were controlled to heat up to 850°C at a heating rate of 20°C / s, and after keeping warm for 10 minutes, they were quenched with water and cooled to room temperature; the metallized fiber-reinforced ceramic-based composite materials of Example 3 and Comparative Example 1 in the quartz lamp array were controlled to heat up to 1000°C at a heating rate of 20°C / s, and after keeping warm for 10 minutes, they were quenched with water and cooled to room temperature; after repeating the aforementioned rapid heating and water quenching and cooling processes 10 times, the coatings of each composite material were observed to see if cracking or deformation occurred, and the bonding performance between the coating and the substrate was tested (specific reference is made to GB / T9286-2021). The specific results are shown in the following table:

[0103] It can be seen that in the preparation of the metallized fiber-reinforced ceramic-based composite material of the present invention, the fiber-reinforced ceramic-based composite material is processed to the predetermined size of the conformal antenna cover (window) as required, and after obtaining the pretreated substrate, nano-boron nitride powder, nano-hafnium nitride powder, and nano-tantalum diboride powder are evenly mixed and treated with a silane coupling agent APTES to obtain a composite reinforced powder; the premixed powder is modified by the silane coupling agent APTES to improve its dispersibility in the interface layer spray slurry and improve its bonding performance with the interface layer coating. Then the composite reinforced powder is mixed with the interface layer coating (polysilazane coating or polysiloxane coating) to obtain the interface layer spray slurry, which is then sprayed onto the surface of the pretreated substrate to form an interface layer; and the addition of the composite reinforced powder inhibits shrinkage, reduces internal stress, and improves the thermal stability, thermal shock resistance and mechanical properties of the interface layer; and improves the bonding performance of the interface layer with the substrate, and forms a mechanical interlock and inhibits interface peeling through the anchoring effect of the composite reinforced powder on the surface of the pretreated substrate; at the same time, through the setting of the interface layer, the wettability problem of the metal layer and the composite material is effectively improved, and the bonding performance of the coating and the substrate is optimized. Then the metallized spray slurry is coated on the interface layer coating area to form a metal layer, and finally, after fine processing, a metallized fiber-reinforced ceramic matrix composite material is obtained; the aforementioned technical means cooperate with each other and work synergistically, which can effectively overcome the problem that the existing metallization method is not suitable for the preparation of conformal antennas for fiber-reinforced ceramic matrix composite materials, as well as the problem that the metallization process is complex and highly dependent on equipment, improve the bonding performance of the metallization layer and the fiber-reinforced ceramic matrix composite material, and improve the stability of the coating.

[0104] Unless otherwise specified, all percentages used in the present invention are by mass.

[0105] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a metallized fiber-reinforced ceramic matrix composite material, characterized in that: The method comprises the following steps: pretreatment of substrate, preparation of composite reinforced powder, preparation of interface layer, preparation of metal layer and fine processing; The substrate pretreatment includes processing the fiber-reinforced ceramic matrix composite material to the size of a conformal antenna, and then performing surface polishing and defect repair to obtain a pretreated substrate; In the preparation of the composite reinforced powder, nano boron nitride powder, nano hafnium nitride powder and nano tantalum diboride powder are uniformly mixed to obtain a premixed powder; The premixed powder is treated with silane coupling agent APTES to obtain composite reinforced powder; The interface layer is prepared by uniformly mixing the interface layer coating, solvent and composite reinforcing powder to obtain an interface layer spray coating slurry; spraying the interface layer spray coating slurry onto the surface of the pretreated substrate, drying and sintering, to obtain a substrate with an interface layer formed on the surface; The interface layer coating is a polysilazane coating or a polysiloxane coating; The metal layer is prepared by spraying the metallized spray slurry onto the interface layer surface of the substrate, followed by drying and sintering to obtain a substrate with a metal layer formed on the surface.

2. The method for preparing the metallized fiber-reinforced ceramic matrix composite material according to claim 1, characterized in that: In the substrate pretreatment, defect repair is to use a repair liquid to spot-coat the defect and then sinter; The repair liquid is composed of the following raw materials in parts by weight: 35-45 parts of silica sol, 1-5 parts of boric acid, and 55-65 parts of submicron ceramic powder; The submicron ceramic powder is selected from: silicon oxide, aluminum oxide, and mullite.

3. The method for preparing the metallized fiber-reinforced ceramic matrix composite material according to claim 1, characterized in that: In the preparation of the composite reinforced powder, the premixed powder is put into an ethanol solution, stirred and heated to 55-60° C., kept warm and dripped with a silane coupling agent APTES; after the silane coupling agent APTES is dripped, the solution is kept warm and stirred for 4-5 hours, and a solid is separated and obtained, and the solid is washed with water and then dried to obtain the composite reinforced powder.

4. The method for preparing the metallized fiber-reinforced ceramic matrix composite material according to claim 1, characterized in that: In the preparation of the composite reinforced powder, the mass ratio of nano boron nitride powder, nano hafnium nitride powder and nano tantalum diboride powder is 3-3.5:5-6:1-1.2; The mass ratio of the premixed powder to the silane coupling agent APTES is 1:0.2-0.

25.

5. The method for preparing the metallized fiber-reinforced ceramic matrix composite material according to claim 1, characterized in that: In the preparation of the interface layer, the mass ratio of the interface layer coating, the solvent, and the composite reinforcing powder is 84-88:32-40:12-16; The spraying pressure of the interface layer spray slurry is 0.2-0.3MPa, and the spraying weight gain is controlled at 100cm 2 The spray weight on the pre-treated substrate surface is 0.4-0.6g.

6. The method for preparing the metallized fiber-reinforced ceramic matrix composite material according to claim 1, characterized in that: In the preparation of the interface layer, the drying temperature is 85-100° C. and the drying time is 0.5-1 h; The sintering temperature is 750-850℃ and the sintering time is 15-30min; The thickness of the interface layer is 6-10 μm.

7. The method for preparing the metallized fiber-reinforced ceramic matrix composite material according to claim 1, characterized in that: In the preparation of the metal layer, the metallization spraying slurry contains metal slurry and diluent; The metal slurry is one of the following: silver slurry, gold slurry, platinum slurry, silver-palladium alloy slurry; The diluent is an ethanol or propanol solution of butyl carbitol or terpineol; The mass ratio of metal slurry to diluent is 65-75:25-35.

8. The method for preparing the metallized fiber-reinforced ceramic matrix composite material according to claim 1, characterized in that: In the preparation of the metal layer, the spraying pressure of the metallization spray slurry is 0.2-0.3 MPa, and the spraying weight gain is controlled to be 100 cm 2 The spray weight on the interface layer surface is 1-1.5g; The drying temperature is 120-150°C and the drying time is 0.5-1h; The sintering temperature is 750-850℃ and the sintering time is 10-15min; The thickness of the metal layer is 8-15 μm.

9. The method for preparing the metallized fiber-reinforced ceramic matrix composite material according to claim 1, characterized in that: The finishing process comprises finishing the metal layer of the conformal antenna radiation area by laser etching to obtain a metallized fiber-reinforced ceramic matrix composite material for the conformal antenna; The laser etching uses a 3D galvanometer to control the laser direction and uses a picosecond laser for etching; The laser power of the laser etching is 2-5W, the linear speed is 300-500mm / s, and the etching times are 2-4 times.

10. A metallized fiber-reinforced ceramic matrix composite material, characterized in that: The method is prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • High-temperature-tolerance frequency selection wave-transmitting structure and preparation method thereof

    CN106630979A

  • Frequency-selective fiber-reinforced ceramic-based wave-transparent material and preparation method thereof

    CN109704796A

  • Metallized ceramic matrix composite material and curved surface metallization method

    CN112552079A

  • Preparation method of semi-inorganic heat-insulating and wave-permeable coating material

    CN103396738A

  • Preparation method of ceramic-based electronic circuit

    CN108558413A

Cited By

  • Preparation method of oil-resistant and wear-resistant coating for surface of antenna tube

    CN120699510A